Understanding and Preventing Gender-based Violence in the Anglophone Caribbean: A Multi-disciplinary Endeavor (KULT_online, 2023)
The edited volume Critical Caribbean Perspectives on Preventing Gender-Based Violence insightfully explores the complex topic of GBV in the Caribbean. Its multi-disciplinary contributions emphasize the need to approach GBV multidimensionally to do justice to the complex and intricate nature of the topic. In particular, the volume facilitates a discussion about aspects of GBV that have not gained a lot of attention, and are mostly invisible or even silenced in public discourse.